Transformacja systemów politycznych Polski i Ukrainy: charakterystyka porównawcza głównych tendencji - Sribna, Tatiana (Wydział Nauk Politycznych i Dziennikarstwa UAM w Poznaniu, 2011)
This paper is a comparative analysis of the characteristic and most important trends in the development of political systems in Poland and Ukraine. It concerns the major issues pertaining to the post-soviet neo-patrimonial system, the structuring of political and economic processes, and the zone of genuine political struggle. The paper also indicates the major tendencies in the development of the political system in Ukraine.
The Transformation of Political Systems in Poland and Ukraine: A Comparative Characteristics of the Main Trend